Enhanced broadband monopole emission and acoustic energy harvesting via a dual anisotropic metamaterial. (29th October 2021) - Lei, Yunzhong; Wu, Jiuhui; Huang, Zhen; Yang, Shaokun
Abstract: Broadband sound energy enhancement is essential in practical scenarios, such as acoustic positioning and acoustic communication. In this paper, a dual anisotropic metamaterial composed of an inner Mie resonator and an outer acoustic grating is proposed, aiming to achieve enhanced broadband monopole emission and acoustic energy harvesting (AEH) via the coupling of the first and second monopole resonances. Considering thermo-viscous dissipation, numerical simulations and experimental results demonstrate that the dual anisotropic metamaterial can realize omnidirectional enhanced broadband monopole emission at 795 Hz–1511 Hz, the maximum sound pressure level (SPL) gain is 16.4 dB and the SPL gain fluctuation is 3 dB. Furthermore, simulation results reveal that the broadband AEH can be achieved by the dual anisotropic metamaterial, the fluctuation of the SPL gain at 794 Hz–1537 Hz is 3 dB and the maximum is 14.7 dB. Based on the results, the dual anisotropic metamaterial is expected to show significant potentials in acoustic positioning and acoustic communication.